2011
DOI: 10.1007/s10533-011-9641-8
|View full text |Cite
|
Sign up to set email alerts
|

A trait-based framework for predicting when and where microbial adaptation to climate change will affect ecosystem functioning

Abstract: As the earth system changes in response to human activities, a critical objective is to predict how biogeochemical process rates (e.g. nitrification, decomposition) and ecosystem function (e.g. net ecosystem productivity) will change under future conditions. A particular challenge is that the microbial communities that drive many of these processes are capable of adapting to environmental change in ways that alter ecosystem functioning. Despite evidence that microbes can adapt to temperature, precipitation reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
247
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(251 citation statements)
references
References 84 publications
3
247
0
1
Order By: Relevance
“…In addition, this strong correlation also indicates that functional genes can be used to develop a gene-centric approach to integrate environmental genomics into simulation models in order to improve their predictive power and accuracy of ESMs (Reed et al, 2014). Regulatory pathways of the activity of enzymes involved in C degradation Identifying the structural-functional relationships for microbial organisms is particularly critical to determine the importance of the soil microbial community in regulating ecosystem processes, and thus there is keen interest in developing theoretical and experimental approaches to disentangle the microbial regulation of soil functions from other biotic and abiotic drivers (for example, Strickland et al, 2009;Wallenstein and Hall, 2012;Talbot et al, 2014;You et al, 2014;Wood et al, 2015). Albeit we found that functional genes were strongly related to enzyme activities, these results are correlative in nature and hence potentially non-causative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this strong correlation also indicates that functional genes can be used to develop a gene-centric approach to integrate environmental genomics into simulation models in order to improve their predictive power and accuracy of ESMs (Reed et al, 2014). Regulatory pathways of the activity of enzymes involved in C degradation Identifying the structural-functional relationships for microbial organisms is particularly critical to determine the importance of the soil microbial community in regulating ecosystem processes, and thus there is keen interest in developing theoretical and experimental approaches to disentangle the microbial regulation of soil functions from other biotic and abiotic drivers (for example, Strickland et al, 2009;Wallenstein and Hall, 2012;Talbot et al, 2014;You et al, 2014;Wood et al, 2015). Albeit we found that functional genes were strongly related to enzyme activities, these results are correlative in nature and hence potentially non-causative.…”
Section: Discussionmentioning
confidence: 99%
“…Blankenship et al 2011;Wallenstein and Hall 2011), which may provide new selection pressures on plants via plant-soil feedbacks (e.g. Lau and Lennon 2011;Fig.…”
Section: Linkages Between Plant Genetics and Soilsmentioning
confidence: 99%
“…Recent attempts to link microbial communities and environmental biogeochemistry have yielded mixed results [1][2][3][4][5][6], leading researchers to propose the inclusion of community assembly mechanisms such as dispersal and selection in our understanding of biogeochemistry [2,[7][8][9]. Although much work has examined how assembly processes influence the maintenance of diversity and other ecosystem-level processes in macrobial systems [10][11][12][13], our comprehension of how these processes influence microbially-mediated biogeochemical cycles is still nascent [2,8,14].…”
Section: Introductionmentioning
confidence: 99%